2009
DOI: 10.1002/ajmg.a.33039
|View full text |Cite
|
Sign up to set email alerts
|

X‐linked brachytelephalangic chondrodysplasia punctata: A simple trait that is not so simple

Abstract: Brachytelephalangic chondrodysplasia punctata (CDPX1) is an X-linked recessive disorder caused by mutations in the arylsulfatase E (ARSE) gene, characterized by the presence of stippled epiphyses on radiograms in infancy and early childhood. Other features include hypoplasia of the midface and of the nasal bone, short stature, brachytelephalangy, and ectopic calcifications. Patients display marked clinical variability and there is no clear genotype-phenotype correlation. We report on a 14-month-old boy who pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Mutations in the ARSE gene cause X-linked brachytelephalangic chondrodysplasia punctata ( CDPX1 ; OMIM #302950), a congenital disorder of bone and cartilage development also characterized by short stature [12]. The co-localization of human growth syndrome genes with SNPs associated with adult height has been reported in European-ancestry samples [3], [13], [14].…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in the ARSE gene cause X-linked brachytelephalangic chondrodysplasia punctata ( CDPX1 ; OMIM #302950), a congenital disorder of bone and cartilage development also characterized by short stature [12]. The co-localization of human growth syndrome genes with SNPs associated with adult height has been reported in European-ancestry samples [3], [13], [14].…”
Section: Resultsmentioning
confidence: 99%
“…Calcification in these disorders can be either diffuse or punctate. Stippled epiphyses have typically been considered a necessary criterion for CDPX1 diagnosis, but Casarin et al [ reported on a 14‐month‐old boy with ARSE deletion who did not have stippled epiphyses. Stippled epiphyses have also been reported in patients with KS [Say et al, ; Cormode et al, ; Ziereisen et al, ] although not as commonly as in those with CDPX1.…”
Section: Discussionmentioning
confidence: 99%
“…However, eight of 29 reported patients with KS, including Patient 3 in this series, did not have congenital heart disease (reports by Miller [ and Munroe et al [ did not address cardiac evaluation and therefore these three patients are not included in the denominator). Diffuse tracheobronchial tree calcification and stenosis is a major cause of morbidity in patients with KS but has also been reported in at least two patients with ARSE ‐mutation associated CDPX1 [Wolpoe et al, ; Casarin et al, ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, nine mothers of previously reported males with CDPX1 who had carrier testing were found to be carriers. 3,25,27 Maternal carriers were identified among both ARSE deletion and point mutation alleles (see Table 2). We suggest that the high frequency of maternal carriers, if proven, could be secondary to de novo mutations occurring more often in the germline of the maternal grandfather.…”
Section: Discussion Spectrum Of Arse Mutationsmentioning
confidence: 99%